Marine Invertebrate Metabolites with Anticancer Activities: Solutions to the “Supply Problem” - Nelson G. M. Gomes; Ramesh Dasari; Sunena Chandra; Robert Kiss; Alexander Kornienko (Marine Drugs, 2016)
Marine invertebrates provide a rich source of metabolites with anticancer activities and several marine-derived agents have been approved for the treatment of cancer. However, the limited supply of promising anticancer metabolites from their natural sources is a major hurdle to their preclinical and clinical development. Thus, the lack of a sustainable large-scale supply has been an important challenge facing chemists and biologists involved in marine-based drug discovery. In the current review we describe the main strategies aimed to overcome the supply problem. These include: marine invertebrate aquaculture, invertebrate and symbiont cell culture, culture-independent strategies, total chemical synthesis, semi-synthesis, and a number of hybrid strategies. We provide examples illustrating the application of these strategies for the supply of marine invertebrate-derived anticancer agents. Finally, we encourage the scientific community to develop scalable methods to obtain selected metabolites, which in the authors’ opinion should be pursued due to their most promising anticancer activities.